Quality assessment and chemical diversity of Australian propolis from Tetragonula carbonaria and Tetragonula hockingsi stingless bees - Damon C. Woods; Malin A. Olsson; Tim A. Heard; Helen M. Wallace; Trong D. Tran (Scientific Reports)
Abstract Stingless bee propolis has gained global attention as a novel source of bioactive compounds with potential applications in food and medicine to promote human health. However, research on Australian stingless bee propolis remains limited as much of propolis is discarded by Australian beekeepers due to a lack of understanding its value. This study aimed to assess and compare the quality and chemical diversity of propolis from two Australian stingless bee species Tetragonula carbonaria and Tetragonula hockingsi across Queensland and New South Wales. Chemical assays revealed that T. hockingsi propolis had significantly higher total phenolic and flavonoid contents than T. carbonaria. Australian stingless bee propolis also showed high phenolic but moderate flavonoid content compared to international propolis sources. The phenolic content displayed geographical dependence, decreasing from northern to southern regions. The analyses of uHPLC-QTOF MS and 1H NMR profiling identified nine distinct propolis types, showcasing diverse chemical composition with the presence of flavan-3-ol, dihydroflavonol, flavanone, tannin, lignan, phenolic acid, cinnamic acid glycoside, chalcone, and alkyl-phenylketone compounds. These findings provide a foundation for future research into the value and therapeutic potential of Australian stingless bee propolis products, contributing to the development of the Australian propolis industry.